Find the sum of all integers n such that 2 ≤ n ≤ 1 0 0 and ϕ ( n ) n is an odd integer, where ϕ ( n ) denotes the number of positive integers less than n coprime to n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
MSTang, your statement is wrong:
If ϕ ( n ) n is an integer, then it is an odd integer.
Don't forget when its only prime factor is 2 .
Log in to reply
Yeah, when n = 2 k , φ ( n ) n = 2 .
Well, the interesting discovery would be that whenever ϕ ( n ) n is an integer, it must be either 2 or 3 . Hmm, I should have stored this for Proofathon...
Let π 2 ( n ) denote the highest power of 2 that divides n . For example, 4 0 = 2 3 × 5 , so π 2 ( 4 0 ) = 3 . Observe that for ϕ ( n ) n to be an odd integer, we must have π 2 ( n ) = π 2 ( ϕ ( n ) ) .
*Lemma: * If g cd ( a , 2 ) = 1 and b is any integer, π 2 ( a b ) = π 2 ( b ) .
*Proof: * Trivial
*Lemma: * For all a 1 , a 2 , ⋯ , a n , π 2 ( a 1 a 2 ⋯ a n ) = π 2 ( a 1 ) + π 2 ( a 2 ) + ⋯ + π 2 ( a n ) .
*Proof: * Also trivial; left to the reader
*Claim: * If π 2 ( n ) = π 2 ( ϕ ( n ) ) , then n = 2 m p j for some positive integers m , j , where p is a prime of the form 4 k + 3 .
*Proof: * Let n = 2 a 0 × p 1 a 1 p 2 a 2 ⋯ p n a n , where p 1 , p 2 , ⋯ , p n are odd primes and a 0 , a 1 , ⋯ , a n are positive integers. We then have π 2 ( n ) = a 0 . Since ϕ ( n ) is always even, a 0 cannot be zero. Again, since π 2 ( ϕ ( 2 m ) ) = π 2 ( 2 m ( 1 − 2 1 ) ) = m − 1 , n = 0 . Now, note that ϕ ( n ) = = n ( 1 − 2 1 ) ( 1 − p 1 1 ) ⋯ ( 1 − p n 1 ) 2 a 0 − 1 p 1 a 1 − 1 p 2 a 2 − 1 ⋯ p n a n − 1 p 1 a 1 − 1 p 2 a 2 − 1 ⋯ p n a n − 1 ( p 1 − 1 ) ( p 2 − 1 ) ⋯ ( p n − 1 ) Since g cd ( 2 , p 1 a 1 − 1 p 2 a 2 − 1 ⋯ p n a n − 1 ) = 1 , π 2 ( ϕ ( n ) ) = = a 0 − 1 + π 2 ( ( p 1 − 1 ) ( p 2 − 1 ) ⋯ ( p n − 1 ) ) a 0 − 1 + π 2 ( p 1 − 1 ) + π 2 ( p 2 − 1 ) + ⋯ + π 2 ( p n − 1 ) This has to be equal to a 0 , so π 2 ( p 1 − 1 ) + π 2 ( p 2 − 1 ) + ⋯ + π 2 ( p n − 1 ) = 1 Observe that p 1 − 1 , p 2 − 1 , ⋯ , p n − 1 are all even, so π 2 ( p i − 1 ) ≥ 1 for all i . Then, i = 1 ∑ n π 2 ( p i − 1 ) ≥ n Since this has to be equal to 1 , we find out n = 1 . So, n = 2 m p n for some prime p . Also, π 2 ( p − 1 ) = 1 . If p is of the form 4 k + 1 , 4 ∣ p − 1 , and hence π 2 ( p − 1 ) > 1 . So, p must be a prime of the form 4 k + 3 . QED
Now, let n = 2 m ( 4 k + 3 ) n . We then find out ϕ ( n ) = 2 m − 1 ( 4 k + 3 ) n − 1 ( 4 k + 2 ) = 2 m ( 4 k + 3 ) n − 1 ( k + 1 ) . Then, ϕ ( n ) n = = = 2 m ( 4 k + 3 ) n − 1 ( k + 1 ) 2 m ( 4 k + 3 ) n k + 1 4 k + 3 4 − k + 1 1 The only possible solution is k = 0 , so n = 2 m 3 n for some positive integers m and n . Indeed, we can verify that in this case, ϕ ( n ) n = 3 . Quickly listing all possible such numbers from 2 to 1 0 0 , we find out that the set of valid n is { 6 , 1 2 , 1 8 , 2 4 , 3 6 , 4 8 , 5 4 , 7 2 , 9 6 } . The sum is 3 6 6 .
The standard notation for your π function is v 2 ( n ) .
Problem Loading...
Note Loading...
Set Loading...
Let the distinct prime factors of n be p 1 , … , p k . Then,
ϕ ( n ) = n ( 1 − p 1 1 ) … ( 1 − p k 1 ) = n ( p 1 p 1 − 1 ) … ( p k p k − 1 ) , so
ϕ ( n ) n = ( p 1 − 1 p 1 ) … ( p k − 1 p k ) .
Since this is an integer, it must be that ( p 1 − 1 ) … ( p k − 1 ) divides p 1 … p k . We investigate this very strong condition.
First, if all of the p i are odd, then ( p 1 − 1 ) … ( p k − 1 ) is even, while p 1 … p k is odd, so the condition cannot hold. Thus, one of the p i , say p 1 , must equal 2 , and the other p i must be odd. Our condition becomes
( 2 − 1 ) ( p 2 − 1 ) … ( p k − 1 ) ∣ 2 p 2 … p k or
( p 2 − 1 ) … ( p k − 1 ) ∣ 2 p 2 … p k . Now, note that the right-hand side has exactly one factor of 2 , since all of p 2 , … , p k are odd; since the left-hand side is composed of even factors, we can only have one factor on the left-hand side. That is, our condition reduces to just
p 2 − 1 ∣ 2 p 2 . Then there must be some positive integer a such that 2 p 2 = a ( p 2 − 1 ) , or 2 p 2 = a p 2 − a . Taking mod p 2 , we get a ≡ 0 ( m o d p ) . So, we let a = b p 2 for some positive integer b , and the equation becomes
2 p 2 = ( b p 2 ) p 2 − b p 2 which gives
2 = b ( p 2 − 1 ) . This means that p 2 − 1 is either 1 or 2 ; in the first case, we get p 2 = 2 , which contradicts the assumption that the p i are distinct; therefore the second case must hold, so p 2 = 3 .
Thus, n = 2 c 3 d for some positive integers c , d . This implies that ϕ ( n ) = n ⋅ 2 1 ⋅ 3 2 = 3 n , so ϕ ( n ) n = 3 . (This is an interesting discovery - if ϕ ( n ) n is an integer, then it is an odd integer.) So, all n in the form 2 c 3 d work. Going through all cases, we get the possible values
n = 6 , 1 8 , 5 4 , 1 2 , 3 6 , 2 4 , 7 2 , 4 8 , 9 6 , the sum of which is 3 6 6 .